2020
DOI: 10.3390/su12208498
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Care in a Familialist Regime: Coping with Elderly Care in Slovenia

Abstract: In countries with prevalent family care and less developed care services, it is important to understand the ways families cope with the care needs of their frail family members as part of policy learning to make care systems more sustainable. Filial care is a vital element of family care, yet is significantly restrained by the involvement of carers in the labour market; unequal gender distribution of the care burden; and insufficient recognition of, and policy support, for family care. This article considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…This study confirms that in the two study countries, adolescents are part of older and disabled people’s informal care networks, and that taking on the role of carers can often follow a family code ethic according to which GrPs are expected to look after younger grandchildren and older grandchildren are expected to take care of their frail GrPs [ 62 , 63 , 64 , 65 , 66 , 67 ]. Moral rules and principles indeed differentiate good and less good behaviour and describe obligations that family members have for each other.…”
Section: Discussionsupporting
confidence: 77%
“…This study confirms that in the two study countries, adolescents are part of older and disabled people’s informal care networks, and that taking on the role of carers can often follow a family code ethic according to which GrPs are expected to look after younger grandchildren and older grandchildren are expected to take care of their frail GrPs [ 62 , 63 , 64 , 65 , 66 , 67 ]. Moral rules and principles indeed differentiate good and less good behaviour and describe obligations that family members have for each other.…”
Section: Discussionsupporting
confidence: 77%
“…A study on elderly living in Slovakia [33] identified three categories of factors influencing their quality of life: demographic factors, containing age and sex, socio-economic factors, containing marital status, education and income, and health factors containing functional status, anxiety and depression. Quality of life may be also influenced by the characteristics of dwellings [34] or involvement in recreational activities [35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the contrary, the older adults' willingness to access care services should not bear any additional cost for their offspring. This reveals the traditional parent-children's perception of 'filial piety' and 'mutual aid', which influences their spectrum of willingness-to-pay for eldercare services and might be different from family regimes in other cultures (see Hrast et al, 2020).…”
Section: Discussion-sustainable Future Of Eldercare Servicesmentioning
confidence: 99%
“…In a familialist regime, how families cope with care needs and how policies support them become vital for the sustainable development of eldercare services (Hrast et al, 2020). Since daily activities of living (DAL), instrumental daily activities of living (IDAL), and cognitive impairment (Connolly et al, 2017) are much more severe in older adults aged 80 + , these are more in need of assisted or dependent living and deserve higher priority in social inclusion for eldercare services, especially if they have limited family/financial support.…”
Section: An Inclusion-driven Approachmentioning
confidence: 99%